COMPARISON OF BRONCHOALVEOLAR LAVAGE CYTOLOGY AND TRANSBRONCHIAL BIOPSY IN THE DIAGNOSIS OF CARCINOMA OF LUNG - Ahmed, Ayesha; Ahmed, Sajjad (Journal of Ayub Medical College Abbottabad, 2004)
Background: The objectives of this study were to compare bronchoalveolar lavage (BAL) cytology and transbronchial biopsy in the diagnosis of carcinoma lung and to determine accuracy of BAL cytology using histopathologic examination of transbronchial biopsy as gold standard at our center. Methods: This study was carried out at Department of Histopathology, Ayub Medical College, Abbottabad, from 1-9-2000 to 28-2-2003. BAL fluid and bronchial biopsy were received and processed simultaneously. Four cytology and a set of histopathology slides were prepared. These were screened and diagnosis recorded. Sensitivity, Specificity, False Positive, False Negative, Positive predictive value and Negative predictive value of BAL cytology were determined using histopathology of transbronchial biopsy as gold standard. Results: We found the sensitivity of BAL cytology to be 93.44% as compared with transbronchial biopsy. The specificity was 100%. There was no false positive while false negative results were 6.55%. The positive predictive value was 100%, while the negative predictive value was 75%. The overall diagnostic efficacy of BAL cytology was 94.52%. Conclusion: BAL cytology is a highly sensitive and specific test for diagnosis of carcinoma lung. It can be used as a quick and reliable diagnostic method for diagnosis of lung malignancy. Keywords: bronchoalveolar lavage, cytology, lung, carcinoma, biopsy